Analysis of Sawdust and Coal Biomass Fuel Variations on the Efficiency of 660 MW Multistage Turbine Steam Power Plant - Mokh Ausin Al Qoroni; Issafira, Radissa Dzaky; Rizki, Muhammad Daru Fatkhur; Wardana, Vrischo Candra Kumara (Jurnal Rekayasa Mesin, 2025)
The use of biomass as an alternative fuel in power generation systems is an important strategy in supporting the clean energy transition. This study analyzes the effect of variations in the mixture of biomass fuel in the form of sawdust with coal on the efficiency of a 660 MW multistage turbine in a Steam Power Plant (PLTU). The study was conducted experimentally with six variations of sawdust mixture from 0% to 5%. Data were obtained from direct observation and secondary data, then analyzed quantitatively using calculations of isentropic efficiency, turbine power, turbine heat rate, thermal efficiency, and exhaust emissions. The results showed that increasing the percentage of sawdust caused a decrease in the isentropic efficiency of the three types of turbines, namely High Pressure Turbine (HPT) from 85.90% to 83.20%, Intermediate Pressure Turbine (IPT) 98.01% to 96.89%, and Low Pressure Turbine (LPT) from 88.64% to 88.03%, output power from 639.150 MW to 603.525 MW, and thermal efficiency from 45.16%. to 44.04%, as well as an increase in turbine heat rate from 7971.761 kJ/kWh to 8174.373 kJ/kWh. However, flue gas emissions decreased significantly such as SO₂ from 354.898 mg/Nm³ to 11.507 mg/Nm³ and NOₓ from 220.549 mg/Nm³ to 140.324 mg/Nm³, while CO₂ remained relatively stable. The decrease in efficiency is due to the characteristics of sawdust, which has a lower heating value and higher moisture content than coal.